Board structure, free cash flow and dividend per share in Malaysia listed firms: an empirical study of interaction effect - Norazlan Alias; Mohd. Hasimi Yaacob; Ruzita Abdul Rahim; Fauzias Mat Nor (School of Social, Development and Environmental Studies, Faculty of Social Sciences and Humanities, Universiti Kebangsaan Malaysia, 2016)
One of a firm’s major financial decisions that lies in the hands of the board of directors is dividend policy which has long been linked to the firm’s profitability and performance. From the shareholders’ viewpoint, profitability does not necessarily add value to their wealth unless and until it translates into dividend payment and price appreciation.Therefore, how corporate governance via board structure influences the use of free cash flow and how this interaction affects dividend payment are crucial. This study examined the interaction effects of firm’s characteristics such as board structure and free cash flow on divided per share as a proxy of firm’s performance. The fixed effect regression with a sample of 361 non-financial Malaysian listed firms over the period of 2002 to 2007 were employed in the analysis. The interaction between board structure, independent directors , board size and free cash flow revealed that duality weakens the positive effect of free cash flow on dividend, while independent directors strengthen the positive effect of free cash flow on dividend payment. Overall, the results of this study may be surmised to suggest that large number of independent directors in the board of directors benefits the firms in the use of free cash flow, leading to an increase in distributable income to shareholders; but the existence of duality role does not benefit firms in the use of free cash flow, leading to a decrease in distributable income to shareholders. However, board size does not have an effect on the use of free cash flow and performance.